Cultural Perceptions in Bulgarian Educational Institutions: Primary and Secondary Schools - Atanasova, Deana (Media and Language, 2024)
The perception of the ethnic minorities in Bulgaria is generally negative. The reasons for this are found in insufficient awareness and the impact of the media discourse.There is a critical public need to discuss the topic of the multicultural classroom and a growing need to explore the issue of pedagogical multicultural attitudes and cross-cultural competence.The research analyses results from an own empirical study on the topic conducted in 2023 in several cities in the country in primary and secondary schools.
Keywords: ethnicity; otherness; multi-cultural class; intercultural competence; communication; intolerance; stereotypes